On the Modeling of Wear in Grease-Lubricated Spherical Roller Bearings. Issue 5 (2nd September 2020) - Pozzebon, Matthew L.; Lin, Chih-Ling; Meehan, Paul A.
Abstract: This work presents an approach for modeling grease-lubricated bearing wear by coupling models for boundary-lubricated wear and bearing lubrication state. The lubrication model takes a mass balance approach, using previously developed models for pressure-driven side flow loss and centrifugally driven bleed supply mechanisms. These are combined with a contact model to determine the level of surface interaction and the impact that this interaction has on the lubricated wear and friction coefficients. The developed model was used in numerical simulation of the wear over time during operational conditions representative of 2 Mkm travel distance of a passenger train and the results were compared with experimental investigation of wear particles collected from field test lubricating grease. The results suggest nonlinear behavior with an increasing wear rate over time. Comparison between model results and wear volume estimated from collected wear particles is inconclusive and requires further investigation. A sensitivity analysis of the wear rate found that early in life the model is most sensitive to parameters that directly influence contact properties (load, boundary-lubricated friction coefficient, and wear coefficient). At later stages this shifts as parameters that affect the lubricant loss and supply mechanisms (temperature, base oil viscosity, lubricant fill) become equally or more important.